2023
DOI: 10.1002/ijc.34526
|View full text |Cite
|
Sign up to set email alerts
|

FSCN1 as a new druggable target in adrenocortical carcinoma

Abstract: Adrenocortical carcinoma (ACC) is a rare endocrine malignancy with a high risk of relapse and metastatic spread. The actin-bundling protein fascin (FSCN1) is overexpressed in aggressive ACC and represents a reliable prognostic indicator. FSCN1 has been shown to synergize with VAV2, a guanine nucleotide exchange factor for the Rho/Rac GTPase family, to enhance the invasion properties of ACC cancer cells.Based on those results, we investigated the effects of FSCN1 inactivation by CRISPR/Cas9 or pharmacological b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…m6A methyltransferase METTL14 can catalyse m6A methylation modification on mRNA, while reading protein IGF2BP3 can recognize the modification and affect gene expression, thereby affecting gene expression. FSCN1 is closely related to cell motility, EMT, migration, inflammation and immunity and has been reported as a potential therapeutic target for various cancers 20–23 . Interestingly, FSCN1 was predicted to have multiple m6A modification sites on its mRNA sequence through a sequence‐based m6A modification site predictor (http://www.cuilab.cn/sramp/).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…m6A methyltransferase METTL14 can catalyse m6A methylation modification on mRNA, while reading protein IGF2BP3 can recognize the modification and affect gene expression, thereby affecting gene expression. FSCN1 is closely related to cell motility, EMT, migration, inflammation and immunity and has been reported as a potential therapeutic target for various cancers 20–23 . Interestingly, FSCN1 was predicted to have multiple m6A modification sites on its mRNA sequence through a sequence‐based m6A modification site predictor (http://www.cuilab.cn/sramp/).…”
Section: Resultsmentioning
confidence: 99%
“…To validate the influence of HPV16 on the expression of these two inflammation and immunity and has been reported as a potential therapeutic target for various cancers. [20][21][22][23] Interestingly, FSCN1 was predicted to have multiple m6A modification sites on its mRNA sequence through a sequence-based m6A modification site predictor (http:// www.cuilab.cn/sramp/). Using MeRIP-PCR analysis, we found that overexpressing HPV16 E6/E7 increased m6A modification and expression of FSCN1.…”
Section: Upregulation Of Mettl14 and Igf2bp3 Mediated By Hpv16 E6/e7 ...mentioning
confidence: 99%
“…This elevation of FOXM1 subsequently enhanced the expression of downstream cell cycle-related genes CENPA and CENPB, driving cell cycle progression and cell proliferation. Moreover, Facin Actin-bundling Protein 1 (FSCN1) is an important protein that regulates cancer cell migration and invasion ( 91 ). Zhang et al.…”
Section: Roles and Mechanisms Of Circrna In Respiratory Cancersmentioning
confidence: 99%
“…We have demonstrated that NR5A1 overexpression in ACC cells regulates the expression of both positive and negative dosage-dependent target genes which are directly implicated in shaping the malignant tumour phenotype (3)(4)(5)(6)(7)(8). On the other hand, activating mutations in CTNNB1 and other genetic alterations in canonical Wnt pathway components in ACC induce nuclear translocation of beta-catenin and transcriptional regulation of genes involved in cell proliferation, apoptosis and invasion, being also associated to immune cell exclusion from the tumour (16,(26)(27)(28)(29)(30)(31). Overall, these data suggest a model where NR5A1 overexpression and beta-catenin activation principally act in parallel, rather than functionally interacting, to drive ACC malignancy (Figure 3).…”
mentioning
confidence: 99%